Popularitas WhatsApp sebagai media komunikasi dan berbagi informasi akademik mahasiswa - Zakirman Zakirman; Chichi Rahayu (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2018)
Changes in human needs in recent years have been influenced by the rapid development of technology and information delivery. The widespread use of smartphones by individuals in the community is one of the real forms of changing human needs due to the rapid development of technology and information. Based on the survey, 99.2% of students are active users of smartphones. This proves the high consumptive power among students towards the smart phone. This condition is undeniable because of the many features offered by smartphones in facilitating the academic activities of every student, ranging from task searches to sharing information and communicating with all people in the campus world. Communication and information sharing can be done using several applications including: BlackBerry Mesangger (BBM, WhatsApp (WA), Line, Telegram, Email, Twitter, Facebook (FB) etc. Based on the questionnaire that has been distributed, 96.4% of students choose WA as an application that is most often used to communicate and share academic information, followed by the second place is BBM with a percentage of 0.79% of users.This finding is a clear evidence that there has been a significant shift and changes in the number of users from BBM to WA, especially for Millennials like students, supported by a number of reasons including sophisticated protection features, practicality of use and completeness of WA features that make it increasingly excellent and increasingly popular among students.Based on the findings obtained during the research activities, it can be concluded that whatsapp application is the most popular application which is used seb communication media and sharing of student academic information.